Coxiella burnetii Detected in Tick Samples from Pastoral Communities in Kenya. (9th July 2018) - Koka, Hellen; Sang, Rosemary; Kutima, Helen Lydia; Musila, Lillian
Abstract : Ticks are important disease vectors in Kenya with documented evidence of carriage of zoonotic pathogens. Coxiella burnetii is an important tick-borne pathogen that is underreported in Kenya and yet this infection likely contributes to undiagnosed febrile disease in pastoral communities. Archived human blood (278) and tick pool samples (380) collected from five pastoral communities in Kenya were screened for C. burnetii by PCR using primers targeting the transposon-like IS1111 region. All the human blood samples were negative for C. burnetii DNA. However, C. burnetii was detected in 5.53% (21/380) of the tick pools tested. Four of the twenty-one PCR positive samples were sequenced. The findings indicate that Coxiella burnetii was not present in the human blood samples tested. However, C. burnetii was detected in ticks from Mai Mahiu, Marigat, Ijara, Isiolo, and Garissa indicating a natural infection present in the tick vector that poses a risk to livestock and humans in these communities.